Acute appendiceal diverticulitis diagnosed in the postoperative context of appendectomy - Frade, Sofia M.; Andrade, Ana K.; Pimentel, João S.; Moniz, Luis M.; Viegas, Helder J. (International Surgery Journal, 2021)
Acute appendiceal diverticulitis is a rare cause of acute abdomen that is commonly interpreted as acute appendicitis until definitive histological result. We herein present two cases of patients of distinct age groups and gender who presented to the emergency department with right lower quadrant abdominal pain. Laboratory and imaging studies led to the diagnosis of acute appendicitis. In both cases, intraoperative findings were compatible with the initial diagnosis and therefore appendectomy was performed. Later pathological exam showed diverticulitis of the vermiform appendix. Although appendiceal diverticulitis is associated with a higher risk of perforation and neoplasms, both patients had linear postoperative period, without complications or dysplastic findings. Despite its similarities to the acute appendicitis, appendiceal diverticulitis presents itself as a distinct entity and should be suspected in patients with right lower abdominal pain in older age and with longer duration of symptoms.